2015
DOI: 10.1002/chem.201406676
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient AuPd/Carbon Nanotube Nanocatalysts for the Electro‐Fenton Process

Abstract: Developmento fn ovel nanocatalysts for the highly efficient in situ synthesis of H 2 O 2 from H 2 and O 2 in the electro-Fenton (EF) process has potential for the remediation of water pollution. In this work, AuPd/carbonn anotube (CNT) nanocatalysts were successfully synthesized by the facile aggregation of AuPd bimetalso nC NTs. Characterization by X-ray diffraction, transmission electron microscopy,a nd X-ray photoelectronspectroscopy indicated that pure AuPd bimetallic heterogeneousn anospheres( % 20 nm) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 43 publications
1
21
0
Order By: Relevance
“…The most typical and popular magnetite (Fe 3 O 4 ) NPs not only can be easily recycled by magnetic method, but also hold great potential in in-situ providing Fe 2+ in electrocatalysis [25]. In addition, bimetallic alloys (e.g., AuPd) were confirmed by our previous study [26] to be capable of in-situ generating H 2 O 2 from H 2 and O 2 provided by water electrolysis, contributing to the electrocatalytic oxidation of organic pollutants. Considering the aforementioned characteristics, it is proposed that the electrocatalytic oxidation of BMIM can be effectively facilitated by a 3D electrocatalytic system with an integrated AuPd/Fe 3 O 4 PEs.…”
Section: Introductionsupporting
confidence: 56%
See 1 more Smart Citation
“…The most typical and popular magnetite (Fe 3 O 4 ) NPs not only can be easily recycled by magnetic method, but also hold great potential in in-situ providing Fe 2+ in electrocatalysis [25]. In addition, bimetallic alloys (e.g., AuPd) were confirmed by our previous study [26] to be capable of in-situ generating H 2 O 2 from H 2 and O 2 provided by water electrolysis, contributing to the electrocatalytic oxidation of organic pollutants. Considering the aforementioned characteristics, it is proposed that the electrocatalytic oxidation of BMIM can be effectively facilitated by a 3D electrocatalytic system with an integrated AuPd/Fe 3 O 4 PEs.…”
Section: Introductionsupporting
confidence: 56%
“…Briefly, 1.5 mL hydrazine monohydrate (55 vol%), 2 mL FeSO 4 solution (0.5 M), 1 mL NaOH solution (5 M) and 20 mL ethylene glycol were intensive stirred and transferred into a 40 mL stainless steel Teflon autoclave and maintained at 200 C for 24 h. The resulting products were collected, washed and finally dried in a vacuum oven at 40 C for 6 h. AuPd/Fe 3 O 4 PEs were synthesized by a one-step chemical solution deposition method according to our previous work [26]. As illustrated in Fig.…”
Section: Synthesis Of Aupd/fe 3 O 4 Particle Electrodesmentioning
confidence: 99%
“…Recently, it was shown that Pd-based catalysts hold great potential in direct synthesis of H 2 O 2 from electro-generated H 2 and O 2 (Eqs. (4) -(6)), which greatly resolves the problems mentioned above [9,10].…”
Section: Introductionmentioning
confidence: 74%
“…The production of ● OH and HO 2 ● oxidants from Fenton‐like reactions (Equations and ) in the presence of copper can help the performance of the catalyst: Cu++H2O2Cu2++OH+OH Cu2++H2O2Cu++HO2+H+ The aggregation of nanoparticles in catalysts is the other problem that should be overcome. Fixing of nanoparticles on the supports such as activated carbon, carbon nanotube and carbon aerogel can hinder the gathering of nanoparticles. Reduced graphene oxide (rGO) is an ideal selection for the catalyst support, due to its good electrical conductivity, thermal stability and high surface area …”
Section: Introductionmentioning
confidence: 99%